2009
DOI: 10.1111/j.1744-6171.2009.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Recruitment and Retention Rates in Preventive Longitudinal Research with Adolescent Mothers

Abstract: Retention rates for this study were low. With today's technology, many additional strategies need to be employed to improve retention rates with adolescent mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 8 publications
2
43
0
Order By: Relevance
“…Consistent with other studies analyzing recruitment and retention, male sex, non-white race and households with more children were predictors of low participant retention [11, 1419]. A study by Nicholson et al implemented retention strategies in a longitudinal study amongst low-income, ethnically/racially diverse families (with a large proportion of African-Americans); at 12-months they did not find any difference in retention rates by race [20].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with other studies analyzing recruitment and retention, male sex, non-white race and households with more children were predictors of low participant retention [11, 1419]. A study by Nicholson et al implemented retention strategies in a longitudinal study amongst low-income, ethnically/racially diverse families (with a large proportion of African-Americans); at 12-months they did not find any difference in retention rates by race [20].…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, a study by Nota et al concluded that the response rate to a questionnaire administered by phone three months after initial enrollment was significantly higher than by mail or email [12]. For participants who are difficult to reach, oftentimes the most successful means to regain contact is through a family member or an alternate contact [13, 14]. We attempted to address the challenge of frequent primary phone number changes by collecting contact information for an alternate contact at time of enrollment and updating this back-up information at the end of every successful call.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with more mobile populations, such as a group of poor, highly itinerant adolescent mothers, needed constant tracking to maintain their study participation. Researchers counteracted patient loss by actively acquiring alternative contact numbers from friends, relatives, and neighbors to trace the whereabouts of the wandering adolescent mothers [29]. Constant communication and frequent appointment reminders from the research staff before each visit improved follow-up attendance, particularly in social behavior studies of risk reduction for alcoholism, diabetes, and HIV infection [3,15,27,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…7, 8 Furthermore, intermittent telephone service has been documented in low-income populations. 8, 9 …”
Section: Introductionmentioning
confidence: 99%